Nonsurgical Embryo Recovery as a Feasible Tool for Supporting Embryo Biobanks of Locally Adapted Brazilian Sheep and Goats - Fonseca, Jeferson F.; Vergani, Gabriel B. [UNESP]; Lima, Monalisa S. D.; Silva, Kleibe M.; Monteiro, Alexandre W. U.; Ramos, Alexandre F.; Alves, Bruna R. C.; Souza-Fabjan, Joanna M. G.; Oliveira, Maria E. F. [UNESP]; Batista, Ribrio I. T. P. (Mary Ann Liebert, Inc, 2021)
This study assessed the outcomes of nonsurgical embryo recovery (NSER) after superovulation (SOV) in five locally adapted Brazilian breeds of sheep and goats. The objective was to evaluate the feasibility and efficiency of using SOV combined with a less-invasive embryo collection technique for supplying the Brazilian animal gene bank with germplasm from specific genotypes of interest. Morada Nova (n = 20), Santa Ines (n = 20), and Somalis (n = 20) ewes received an intravaginal progesterone (330 mg) device for 9 days, while Caninde (n = 15) and Moxoto (n = 15) goats received an intravaginal medroxyprogesterone acetate (60 mg) device for 6 days. All females received 133 mg of porcine follicle-stimulating hormone (pFSH) administrated in six decreasing doses 12 hours apart, starting 60 hours before device removal, plus 37.5 mu g of d-cloprostenol at the fifth and sixth pFSH dose. Donors in estrus were mated with fertile males. The corpora lutea (CL) number was assessed by ultrasonography 1 day before NSER. On day 6.5 or 7 after estrus, NSER was performed following hormonally induced cervical relaxation. A total of 97% of sheep and 90% of goats responded with estrus, and among those, 91% of sheep and 85% of goats presented a CL. In ewes, the numbers of CL were greater (p < 0.05) in the Santa Ines breed, while similar (p > 0.05) CL numbers were found among the goat breeds. All viable embryos were freezable (excellent and good quality) and the number per donor was 7.8 for sheep and 4.9 for goats. All parameters of NSER efficiency, embryo yield, and fertility post-NSER did not differ (p > 0.05) between breeds among each species. The SOV-NSER procedures applied for an embryo biobank supply of locally adapted Brazilian breeds of small ruminants were efficient regarding production of cryopreservable embryos, and preservation of donor fertility. Therefore, SOV followed by NSER is recommended for embryo biobank assembly in sheep and goats.
Keywords: caprine; ovine; transcervical; cryopreservation; genetic resources conservation; superovulation